Left Ventricular Thrombus Formation After Repair of Anomalous Left Coronary Artery From the Pulmonary Artery. (April 2014) - Freud, Lindsay R.; Koenig, Peter R.; Russell, Hyde M.; Patel, Angira
Although thrombus formation following myocardial infarction in adults is well known, intracardiac thrombosis in children is uncommon. We report the case of a large left ventricular thrombus in an infant with ischemic cardiomyopathy secondary to anomalous origin of the left coronary artery from the pulmonary artery. Given its mobility and protrusion across the aortic valve, the patient underwent urgent thrombus removal through a transaortic approach. There were no embolic or neurologic complications. This case highlights that thrombectomy may be performed safely and successfully in critically ill pediatric patients.